What's stopping you? - poster 2006 (2006)
2006 1960-2000 "What's stopping you? - poster 2006" [EP0214], 2006 This poster was issued as part of the Equal Opportunities Commission's What's Stopping You? campaign in 2006 to encourage equal opportunities and wider aspirations among school students. This image is of a woman footballer as part of the England national football team.